HUBUNGAN KARAKTERISTIK IBU DAN KONDISI BAYIDENGAN KEJADIAN POSTPARTUM BLUES DI PUSKESMASKECAMATAN MATRAMAN JAKARTA TIMUR - Esther Novita Angelia (2021)
Postpartum blues is a mild mood disorder characterized by anxiety, mood swings, more sensitive mothers, hopelessness and fatigue that occurs on the first day to the tenth day after giving birth and can last for several days. The results of interviews with 5 postpartum mothers at the Matraman District Health Center found that 4 out of 5 mothers had never heard of the term postpartum blues or baby blues before. The five postpartum mothers interviewed experienced anxiety, worry, fatigue and lack of sleep after giving birth. This study aims to determine the relationship between the characteristics of the mother and the condition of the baby with the incidence of postpartum blues at the Matraman District Health Center, East Jakarta. This study is a quantitative study with a cross-sectional research design. The sampling technique was total sampling with a total of 67 respondents. Analysis of the data used is the Fisher Exact test. The results showed that there was no significant relationship between age (p value = 0.716), education (p value = 0.671), parity (p value = 0.542), and the condition of the baby (p value = 1,000) with the incidence of postpartum blues at the Matraman District Health Center, East Jakarta. Despite the small number of postpartum blues events at the Matraman District Health Center, the Health Center is expected to provide education about the postpartum blues incidence, including the signs and symptoms of postpartum blues and coping management if the mother experiences postpartum blues.